Lateral differences in maximal grip strength in Czech male tennis players aged 11 - 12 in the context of injury prevention - Kolinský, R.; Zhánel, J. (Studia Sportiva, 2019)
The term laterality indicates the one-sided preference or functional advantage of the stronger, more accurate and coordinated limbs or organs and the brain hemisphere of a human body. In the preference process, more accurate, precise, coordinated and stronger side is chosen from the perspective of motoric functions. Among the general population is about 10-13% of left-handers and in certain sport fields this percentage may (baseball, tennis, box etc.). The left-handed dominance in tennis is considered an advantage. Due to unilateral load, there may be an excessive side-effect in strength differences in tennis and overloading of specific muscle group could lead to an injury. The aim of the research was to identify the levels of somatic and strength characteristics and assess the lateral difference in maximal grip strength of Czech elite male tennis players. The sample consisted of male tennis players, ranging in age from 11 to 12.9 years (n=186) who participated in the regular tests for Czech Tennis Association in years 2000-2018. Base anthropometrics were measured (height, weight) and maximal grip strength of both hands using the hand-held dynamometry (Grip D, Takei). Data came from normal distribution (statistically proven - chi-square test). The basic statistical characteristics were calculated (body height, M=155.08±7.98 cm; body weight, M=43.45±7.13 kg; strength of right hand: M=24.88±4.67 kp; strength of left hand: M=21.70±4.74 kp). It was found that 87.6% of the players (n=163) were right-handed and the remaining 12.4% left-handed (n=23). The assessment of the significance (Cohen´s d) between the dominant (playing) hand for the right-handed and left-handed players showed small effect size (dominant hand right: MRHR=25.11±4.41 kp, dominant hand left: MLHL=26.62±5.65 kp; d=0.30, small) in favor of the left-handed players. The difference between the dominant and the non-dominant hand showed large effect size for the right-handed (dominant hand right vs. hand left; MRHR=25.11±4.41 kp, MRHL=21.01±4.15 kp, d=0.96, large) and medium effect size for the left-handed players (dominant hand left vs. hand right; MLHL=26.62±5.65 kp, MLHR=23.24±5.98 kp, d=0.58, medium). The results showed that the value of 15 % level of strength laterality between dominant and non-dominant hand was exceeded for the right-handed (55.83 %) and left-handed (43.48%) groups ergo the exceeded value could be a cause of injuries. Because of this signals attention should be given during training process for optimizing the required load.